GAYA BAHASA KUMPULAN CERPEN ‘MATA YANG ENAK DIPANDANG’ KARYA AHMAD TOHARI (SEBUAH KAJIAN STILISTIKA) - Ahdi Riyono (Jurnal Semantik, 2016)
This study attemps to describe the language use or stylistics of short stories “Mata yang Enak dipandang written by Ahmad Tohari. The way Tohari expresses his ideas can be seen from his choice of lexicalitems, and sentence constructions. He uses metaphore, simile, personification, tautology, hyperbole, climax, anticlimax, repetition, paradox, and nature words, rhetorical sentences, polisindeton, andasindenton in order to emphasize his ideas, to emerge a wholeherated impression, and to attract reader’s interet. Syntatically, he uses both short and long sentences. They are combined to avoid a monotonous impression.Kata Kunci: Gaya bahasa, Mata Yang Enak Dipandang, Stilistika